Wls expression in the rhombic lip orchestrates the embryonic development of the mouse cerebellum. (23rd June 2017) - Yeung, Joanna; Goldowitz, Daniel
Highlights: Loss of Wls results in a small cerebellum. Loss of Wls leads to diminished nuclear and cytoplasmic β -catenin. Loss of Wls leads to a smaller vermis, smaller rhombic lip and loss of unipolar brush cells. Loss of Wls leads to disorganization of the EGL and, ectopic granule, Purkinje cells and interneurons. Loss of Wls leads to a disrupted Bergmann glial scaffold and aberrant foliation. Abstract: Wntless (Wls) is implicated in the Wnt signaling pathway by regulating the secretion of Wnt molecules. During brain development, Wls is expressed in the isthmic organizer (ISO) and rhombic lip (RL). Wls regulates Wnt1 secretion at the ISO which is required to induce midbrain–hindbrain structures. However, Wls function in the RL is not known. Here, we employed Nestin -cre to delete Wls specifically in the RL during mid-gestation. The loss-of- Wls leads to an abnormal RL during development and cerebellar vermis hypoplasia at birth. The Wls conditional knockout (cKO) has rudimentary foliation with an absence of Bergmann glia fibers in the external germinal layer (EGL). The Wls -cKO cerebellum also exhibits ectopia of several cell types and aberrations in granule cell organization. Finally, there is a loss of 85% of unipolar brush cells. From these findings, Wls-expressing cells in the rhombic lip are implicated in the orchestration of cerebellar development.